PostGIS Cookbook : over 80 task-based recipes to store, organize, manipulate, and analyze spatial data in a PostGIS database - Corti, Paolo (Quick answers to common problems., 2014)
An easy-to-use guide, full of hands-on recipes for manipulating spatial data in a PostGIS database. Each topic is explained and placed in context, and for the more inquisitive, there are more details of the concepts used. If you are a web developer or a software architect, especially in location-based companies, and want to expand the range of techniques you are using with PostGIS, then this book is for you. You should have some prior experience with PostgreSQL database and spatial concepts.